The role of bank capital on the bank lending channel of monetary policy transmission: An application of marginal analysis approach - Thanh Phuc Nguyen; Thi Thu Hong Dinh (Cogent Economics & Finance, 2022)
While there is a large body of research on the bank lending channel of monetary policy transmission and the distributional dependence of this transmission on bank characteristics, the asymmetric effect of bank capital on monetary policy-bank loan supply nexus has been ignored. To fill this void, the new post-estimation approach of marginal analysis based on the two-step system-GMM methodology is conducted for the dynamic panel data of Vietnamese commercial banks covering the period of 2007-2020. The results confirm the inertia related to loan growth and the presence of a monetary policy bank lending mechanism, which is robust across a series of monetary policy instruments and the approach of variable exclusion from the baseline model. In addition to previous empirical evidence on less sensitivity of well-capitalized banks to tightened monetary policy, this study shows the specific range value of bank capital that monetary policy stance has no impact on bank loan supply in a time of monetary restrictions. Furthermore, better capitalized banks could take more advantage of the expansionary monetary policy by lending more. The relevant policy recommendations for policy-makers are also provided to the best practice of monetary policy implementations considering these asymmetric effects.
Keywords: E52; G21; 330; Bank lending mechanism; monetary policy transmission; marginal analysis; bank capital